A neutral point potential control for three‐level neutral‐point‐clamped converters based on the search optimization method of the two degrees of freedom. Issue 8 (6th April 2018) - Guan, Bo; Doki, Shinji
Abstract : To realize the neutral point potential (NPP) control for three‐level neutral‐point‐clamped (TL‐NPC) converters, a novel NPP control based on the search optimization method of the two degrees of freedom is proposed in this paper. It can overcome the low‐frequency NPP fluctuation problem that appears under nearest‐three‐vector pulse width modulation (PWM)‐based NPP control under some operating conditions. Although the traditional dual modulation wave method can also solve the low‐frequency NPP problem, the zero‐sequence voltage is limited under this modulation. It decreases the control domain of the neutral point current ( i o ), which causes serious NPP drift problem especially in some special operating conditions, such as a long dead time, a strong asymmetrical load, or serious switch device inconsistency. The proposed method can expand the control domain of i o by defining a new degree of freedom, thus lifting the limits of the zero‐sequence voltage and searching for the optimal two degrees of freedom. The wider control domain of i o corresponds to a stronger NPP control ability. Experiments are carried out finally to prove the merits of the proposed method, by comparing the switching frequency, the NPP control speed, and the output performance. © 2018 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.